Hofstede’s value dimension : a case study of the Chinese family business succession in the East Coast of Malaysia / Iskandar Hasan Tan Abdullah - Abdullah, Iskandar Hasan Tan (2013)
Family Business inheritance among the Chinese community is a tradition that is known by the business community worldwide. Thus, a family business among the Chinese community in Malaysia is no stranger. In fact, the inheritance of this business provides a unique and exciting dimension to be investigated by the Malaysian business community. The paper explores the empirical evaluation of the influence of the family business inheritance among the Chinese, who managed to overcome obstacles and conflicts through discussion and negotiation. This paper uses correlation test to investigate the effect of inheritance in a family business among the Chinese, by the variable-variables such as power distance, uncertainty avoidance, masculinity vs femininity, individualism vs collectivism, time orientation and impact on value dimension. In addition, this paper uses factor analysis and regression testing to determine the main cause of problems in the family business inheritance among the Chinese community. Primary data collected between August and October 2012 using a questionnaire. Meanwhile, secondary data were gathered through library research and interviews to Chinese traders East Coast of Malaysia. Ironically, the young Chinese showed no interest in family business inheritance. In addition, the study also found that the older generation did not object to the will of young people who are their children. In addition, qualitative studies have found that the reasons for refusal to inherit the family business among the Chinese younger generation is due to the lucrative wages than profit earned through the family business. Several other factors are caused by job status, education level and age factors play a role in influencing them to not inherit the family business among the Chinese younger generation.